2007
DOI: 10.2319/100206-400.1
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Facial Morphometry of Attractive Children and Normal Children in the Deciduous and Early Mixed Dentition

Abstract: Objectives: To identify possible esthetic canons in facial size and shape of Italian children. Materials and Methods:The three-dimensional coordinates of 50 facial landmarks (forehead, eyes, nose, cheeks, mouth, jaw, ears) were collected in 220 healthy reference children (4-9 years old) and in 89 ''attractive'' children of a similar age group selected by a commercial casting organization. Soft-tissue facial angles, distances, and volumes were computed. Comparisons were made with the Student's t-test. Results: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 18 publications
3
56
1
5
Order By: Relevance
“…Along with other scientific and technological advances, newer techniques, such as laser scans, magnetic resonance imaging, ultrasounds * , contact digitalization, and stereophotogrammetry, provide significant changes on the diagnosis process, as these are considered to be non-invasive methods of facial analysis [1][2][3] . Furthermore, analogic data have become digital, opening the possibility for quick, precise, and non-radioactive image captures, which can be simultaneously stored for future analysis as well as shared with patients and colleagues 1,2,[4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Along with other scientific and technological advances, newer techniques, such as laser scans, magnetic resonance imaging, ultrasounds * , contact digitalization, and stereophotogrammetry, provide significant changes on the diagnosis process, as these are considered to be non-invasive methods of facial analysis [1][2][3] . Furthermore, analogic data have become digital, opening the possibility for quick, precise, and non-radioactive image captures, which can be simultaneously stored for future analysis as well as shared with patients and colleagues 1,2,[4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] Orthodontists and maxillofacial surgeons, therefore, should have a deep understanding of the facial characteristics that are currently considered by the public as ''attractive.'' 2,3,6,[7][8][9] psychology, the esthetic appraisal of adult faces depends on various combinations of averageness, symmetry, neoteny (babyness) and youthfulness, and sexual dimorphism.…”
Section: Introductionmentioning
confidence: 99%
“…The faces of attractive children, female adolescents, and adult women share several characteristics of babyness: a large face with a large forehead, a relatively large and more prominent facial middle third, reduced vertical development, full and prominent lips, and a more convex soft tissue facial profile than in the normal coetaneous population. 6,[8][9][10][13][14][15][16][17][18][19][20] In contrast, for postpubertal adolescent boys and adult men, attractiveness seems to be positively influenced by facial markers of high testosterone levels, with a relative increment of the facial lower third (more prominent chin, less prominent lips). 6,[9][10]12,18,20 On the other hand, several studies demonstrated that secular trends and even the cultural background can influence the perception of beauty, at least for adult subjects.…”
Section: Introductionmentioning
confidence: 99%
“…The scientific and technological advances, techniques such as laser scanning, MRI, ultrasound, scan for contact and stereophotogrammetry offer significant changes in the diagnostic process, because they are considered non-invasive methods of facial analysis 5,7,8 . .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the facial analysis in 3D is still limited to laboratories of universities and research centers 8,18 .…”
Section: Go-gn (D) Go-t (D) Sum Go-gn (E) Go-t (E) Summentioning
confidence: 99%